Clozapine-associated secondary antibody deficiency. Issue 6 (December 2019) - Ponsford, Mark J.; Pecoraro, Antonio; Jolles, Stephen
Abstract : Purpose of review: Clozapine has recently been described as a novel cause of secondary antibody deficiency (SAD), associated with long-term therapy. Here we critically review the evidence linking clozapine use to an increased infection risk, describe immunological alterations, and discuss potential mechanisms. Recent findings: Individuals with schizophrenia are at two to five times more likely to develop pneumonia than the general population, in particular, when receiving clozapine. Delayed-onset distinguishes clozapine-associated hypogammaglobulinaemia from agranulocytosis or neutropenia that occur at lesser frequency. Biomarker searches in treatment-resistant schizophrenia highlight an immune signature associated with long-term clozapine use. This includes reduction in class-switched memory B cells, echoing common variable immunodeficiency. Recent identification of a role for dopamine in T follicular helper–B cell interactions may inform future clinical studies. Summary: The detrimental impact of the increased infection risk associated with clozapine necessitates a re-evaluation of the current monitoring strategies as well as further studies to better understand the underlying mechanisms of SAD in this setting. On the basis of available evidence, we suggest simple modifications to clozapine monitoring including integration of routine vaccination, smoking cessation, and assessment of humoral immunity. Further studies are required to understand the role of clozapine in neuroinflammation as well as other potentially autoantibody-mediated diseases.